Modelling the Impact of a Rise in Global Equity Risk Premium: The G Cubed Simulation - Realita Eschachasthi (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
The global disruptions the Covid-19 pandemic, financial crisis, trade tension, and geopolitical issues led to uncertainty across the world economies. The impact either on individual emerging or advanced countries, however, remains unclear. To this end, this study is simulating a shock of a one percent increase in equity risk premium permanently in all sectors in all countries, and focusing on exploring its impact on the United States (US), the United Kingdom (UK), Australia, China, Indonesia, and India. The results reveal that no countries are immune from the short-lived synchronised nuisance. Investment plummeted massively following the profound drop in interest rate, while unemployment suddenly soars, and Gross Domestic Product (GDP) contracted dramatically. In the long run, all economies reverse and converge to the initial condition. Nevertheless, there would be persistent GDP loss and sluggish investment in all economies. Therefore, policy responses should be designed based on strong international cooperation, focusing on fiscal policy to limit the impact of global losing confidence.